The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00276-009-0545-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic basis of anterior and posterior instrumentation of the spine: morphometric study

Abstract: In our morphometric study of the spinal vertebrae, we found differences compared to a number of previous morphometric studies performed mainly on a white population. Also, we documented the individual morphometric differences of the same parameters in the same subgroups. These results emphasize the importance of preoperative computed tomography and conventional radiography of each patient in planning a surgical procedure and selecting the appropriate size of the instruments, thus avoiding possible postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
2
27
2
Order By: Relevance
“…A study by Abuzayed et al conducted in a Turkish population using CT scan reported a mean anteroposterior diameter of 15.6-17.6 mm, which is slightly larger than the values reported in the cadaveric studies conducted by Ebraheim et al (1998; or the present study (14.68 -17.47 mm). The transverse diameter of the vertebral body reported by Abuzayed (2010) is also slightly greater than what we found in the Mexican population (19.17 -23.44 mm). These slight variations may be explained by the differences in race, but they must be taken into consideration during surgical procedures.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…A study by Abuzayed et al conducted in a Turkish population using CT scan reported a mean anteroposterior diameter of 15.6-17.6 mm, which is slightly larger than the values reported in the cadaveric studies conducted by Ebraheim et al (1998; or the present study (14.68 -17.47 mm). The transverse diameter of the vertebral body reported by Abuzayed (2010) is also slightly greater than what we found in the Mexican population (19.17 -23.44 mm). These slight variations may be explained by the differences in race, but they must be taken into consideration during surgical procedures.…”
Section: Discussioncontrasting
confidence: 67%
“…One of the most frequent and complex procedures for this is the placement of transpedicular screws (Kayalioglu et al, 2007;Yusof et al, 2007;Sieradzki et al, 2008;Abuzayed et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Anatomical details and dimensions of cervical vertebrae are very important for cervical Spine instrumentation like Trans pedicle screwing [3]. Many Authors have explained about various dimensions of cervical vertebrae by studying CT scan, Direct measurements in bone specimens (Abuzayed et al [3], pankaj & Nepal et al [4], Sandeep saluja et al [5], Chen chun et al [6],Partha sarathy Banerjee et al [7]).…”
Section: Discussionmentioning
confidence: 99%
“…Many Authors have explained about various dimensions of cervical vertebrae by studying CT scan, Direct measurements in bone specimens (Abuzayed et al [3], pankaj & Nepal et al [4], Sandeep saluja et al [5], Chen chun et al [6],Partha sarathy Banerjee et al [7]). They have spent their valuable time in these analyses.…”
Section: Discussionmentioning
confidence: 99%